Estimated glomerular filtration rate is a biomarker of cognitive impairment in Parkinson’s disease - Qu, Yi; Qin, Qi-Xiong; Wang, Dan-Lei; Li, Jiang-Ting; Zhao, Jing-Wei; An, Ke; Li, Jing-Yi; Mao, Zhi-Juan; Min, Zhe; Xiong, Yong-Jie; Xue, Zheng (Frontiers in Aging Neuroscience, 2023)
Backgrounds: The relationship between kidney function and cognitive impairment in Parkinson’s disease (PD) is poorly understood and underexplored. This study aims to explore whether renal indices can serve as indicators to monitor cognitive impairment of PD. Methods: A total of 508 PD patients and 168 healthy controls from Parkinson’s Progression Markers Initiative (PPMI) were recruited, and 486 (95.7%) PD patients underwent longitudinal measurements. The renal indicators including serum creatinine (Scr), uric acid (UA) and urea nitrogen, as well as UA/Scr ratio and estimated glomerular filtration rate (eGFR) were measured. Cross-sectional and longitudinal associations between kidney function and cognitive impairment were evaluated using multivariable-adjusted models. Results: eGFR was associated with lower levels of cerebrospinal fluid (CSF) Aβ1-42 (P=0.0156) and α-synuclein (P=0.0151), and higher serum NfL (P=0.0215) in PD patients at baseline. Longitudinal results showed decreased eGFR predicted a higher risk of cognitive impairment (HR=0.7382, 95%CI=0.6329-0.8610). Additionally, eGFR decline was significantly associated with higher rates of increase in CSF T-tau (P=0.0096), P-tau (P=0.0250) and serum NfL (P=0.0189), as well as global cognition and various cognitive domains (P<0.0500). The reduced UA/Scr ratio was also linked to higher NfL levels (P=0.0282) and greater accumulation of T-tau (P=0.0282) and P-tau (P=0.0317). However, no significant associations were found between other renal indices and cognition. Conclusions: eGFR is altered in PD subjects with cognitive impairment, and predict larger progression of cognitive decline. It may assist identifying patients with PD at risk of rapid cognitive decline and have the potential to monitoring responses to therapy in future clinical practice.